The Role of Group Counseling in Enhancing Social Skills of Secondary School Students: A Systematic Literature Review - Rendy Rasoki Tanjung; Nor Mita Ika Saputri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Social skills are essential competencies that enable students to interact effectively, build positive relationships, and adapt to social environments in school settings. However, many secondary school students experience difficulties in social interaction, such as poor communication, limited empathy, and ineffective cooperation with peers. Group counseling has been widely implemented as an intervention to address these challenges by providing structured opportunities for interaction, reflection, and social learning. This study aims to systematically review empirical research on the role of group counseling in enhancing social skills among secondary school students. A systematic literature review method was employed following the PRISMA guidelines. Relevant articles published between 2019 and 2024 were retrieved from Sinta-indexed journals, Scopus, and Google Scholar. A total of selected empirical studies were analyzed using thematic analysis. The findings indicate that group counseling interventions are effective in improving students’ communication skills, empathy, self-control, cooperation, and social adjustment. Techniques such as role-playing, group discussion, and experiential activities were identified as key components contributing to positive outcomes. This review highlights that group counseling is most effective when facilitated by competent counselors and supported by a conducive school environment. The study contributes to the counseling literature by providing an integrative synthesis of recent evidence and offers practical implications for school counselors in designing effective group counseling programs to enhance students’ social skills.Â